O aprimoramento cognitivo como bem primário em Rawls - Oliveira Neto, Fortunato Monge de (2015)
The main thesis to be demonstrated in this work is that cognitive enhancement through the use of drugs can be included as a primary good within Rawls' thinking. To develop such notion, the text is structured in two parts. The first part intends to describe the theory of justice as equity in its elements directly related to primary goods. The first information to be verified is the unity of the notion of primary goods in all of Rawls' work. Some elements are modified, for example the distinction of natural and social primary goods. Natural primary goods are intelligence, health, imagination, vigor and chance (luck) and social primary goods are law and liberty, opportunity and power, income and wealth and the social fundaments of self-respect. The perception of some talents such as intelligence has also undergone changes, being altered from "higher intelligence" to "educated intelligence". Such fact highlights education as a primary good that permeates all of Rawls' work in different perspectives. Freedom and self-respect are social-primary goods that will also be deepened. The second part presents the definition of improvement and as to show that the distinction between enhancement and treatment is controversial. The part presents the definition of improvement and as the distinction between enhancement and treatment is controversial. Thus, we have deepened the problems related to practice improvement (enhancement) showing how the concepts of Rawls' primary goods as freedom and self-respect are not in opposition to the practice of improvement, particularly cognitive enhancement. We have shown, instead, that the ban of cognitive improvement could lead to denial of these primary goods. But how could we consider cognitive improvement as a primary social good? What we have done in this thesis is to show how cognitive enhancement is important to ensure that primary products are accessible to citizens, and we rebuilt the process that Rawls uses for choosing his primary goods to test that cognitive enhancement through drugs could perfectly be introduced as such.